Comparative analysis of DNA methylation in tobacco heterochromatic sequences - Kovarík, A; Koukalová, B; Lim, K Y; Matyásek, R; Lichtenstein, C P; Leitch, A R; Bezdek, M (Chromosome research, 2000)
Cytosine methylation levels and susceptibility to drug-induced hypomethylation have been studied in several Nicotiana tabacum (tobacco) DNA repetitive sequences. It has been shown using HapII, MspI, BamHI and Sau3AI methylation-sensitive restriction enzymes that the degree of 5'-mCmCG-3' methylation varied significantly between different repeats. There were almost saturation levels of 5-methylcytosine at the inner (3') cytosine position and variable degrees of methylation at the outer (5') cytosine at the enzyme recognition sites. The non-transcribed high copy satellite sequences (HRS60, GRS) displayed significant heterogeneity in methylation of their basic units while middle repetitive sequences (R8.1, GRD5, 5S rDNA) were more uniformly modified at both cytosine residues. Dihydroxypropyladenine (DHPA) treatment, which is thought to reduce DNA methyltransferase activity by increasing S-adenosylhomocysteine levels, resulted in extensive demethylation of the outer cytosine in all repeats, and the partial hypomethylation of cytosines at the inner positions in less densely methylated repeats such as HRS60 and GRS. The results suggest that hypomethylation of 5'-mCmCG-3' sites with DHPA is a gradual non-random process proceeding in the direction mCmCG-->CmCG-->CCG. The 18S-5.8S-25S rDNA was remarkably hypomethylated relative to the 5S rDNA at all restriction sites studied. Fluorescence in-situ hybridization showed that DNA decondensation within and between the 18S-5.8S-25S and 5S rDNA loci was variable in different nuclei. All nuclei had condensed and decondensed sequence. The chromatin of 18S-5.8S-25S rDNA was more readily digested with micrococcal nuclease than the 5S rDNA suggesting that the overall levels of decondensation were higher for 18S-5.8S-25S rDNA. Variable decondensation patterns within and between loci were also observed for GRS and HRS60. Cytosine methylation of the tobacco repeats is discussed with respect to transcription, overall levels of condensation and overall structure.
Keywords: Repetitive Sequences, Nucleic Acid; cytosin; DNA, Plant; Adenine; nukleotidy; Genome, Plant; restrikční enzymy; Transcription, Genetic; satelitní DNA; Cytosine; Nicotiana; DNA, Satellite; heterochromatin; Heterochromatin; interfáze; repetitivní sekvence nukleových kyselin; kultivované buňky; metylace DNA; Interphase; Plants, Toxic; Blotting, Southern; Nucleotides; genetická transkripce; Cells, Cultured; adenin; DNA Methylation; DNA Restriction Enzymes; DNA rostlinná; Southernův blotting; jedovaté rostliny; tabák; genom rostlinný